Qualidade do solo: construindo o conhecimento em propriedades agrícolas familiares produtoras de fumo orgânico. - Audeh, Samira Jaber Suliman (2010)
The present study approaches the relations between local and scientific soil quality knowledge, in organic tobacco family farms of Canguçu-RS. The farms are characterized by the accomplishment of the agricultural activity in areas where the soil is shallow and mountaious. These characteristics highlight the need to find alternatives for the conservation of their lands. The alternatives are based on changes regarding to the way that farmers understand the nature and to the way they interpret and apply the knowledge acquired throughout years of experience. This knowledge that each farmer has about the peculiarities of his region is an important factor to the success of soil conservation and to the soil quality maintenance. This study has the objective to construct the knowledge of soil quality in organic tobacco family farms based on local and scientific soil knowledge to reach a sustainable agricultural development. The intention was also understand the aspects related to the soil use, soil management and soil conservation and its interactions, and link scientific with popular knowledge. From this work, it was possible to define a set of indicators according to the farmers perception to characterize the soils from their lands. It was also possible to perceive that those farmers possess detailed knowledge of the soil they cultivate and that their perception is based on a dynamic process of soil properties interactions. Finally, it can be concluded that local knowledge (ethnopedology) is important and when it is associated with scientific knowledge can increase the possibilities of the soil conservation success.